PAIN MANAGEMENT IN CIRCUMCISION: A COMPARATIVE STUDY - Dr.Khalid Mahmood (Journal of University Medical & Dental College)
Abstract Objective: To assess the effectiveness and safety of interventions of reducing pain at neonatal circumcision. Study Design: Quasi-experimental design Place and Duration of Study: Departments of Pediatric Surgery and Plastic Surgery, Allied Hospital, Madina Teaching Hospital, Faisal Hospital, Abdullah Medical Complex, Jail Road, Faisalabad from June 2005 to July 2010. Methodology: Neonates presenting for circumcision during the first month of life were included in the study. A total of 102 neonates were enrolled in this study. Plastibell was used in all cases. They were divided into two groups. Group A(n=51) received dorsal penile nerve block(DPNB)& ring block by injecting lignocaine along with sucrose solution 25%. Group B(n=51) received 20 ml of 25% sucrose solution only during procedure. The pain was assessed by measuring physiological changes e.g.pulse rate, oxygen saturation and crying time. Results: There were significant differences among the groups A and B with respect to physiological changes associated with the pain from the procedure. The group A has marked reduction in pain as compared with group B. Conclusion: These findings suggest that sucrose along with DPNB & ring block is an effective method for the management of pain during circumcision with plasti bell. It has marked reduction in physiological change like heart rate and crying time as compared with sucrose solution alone.